2009
DOI: 10.2298/jsc0904441s
|View full text |Cite
|
Sign up to set email alerts
|

Composite material based on an ablative phenolic resin and carbon fibers

Abstract: In this study, a technological procedure for the production of a molding compound based on short carbon fibers and an ablative phenol-formaldehyde resin for high temperature application was optimized. The starting raw materials were characterized and molding compounds with different fiber/ /matrix ratios and different fiber lengths were obtained. From the different laboratory samples, molded parts were made by thermocompression. The basic mechanical and thermal properties of the composites were determined. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Ablation testing of the composite specimens was accomplished according to the ASTM E285‐08 . Experimental setup for ablation testing is displayed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Ablation testing of the composite specimens was accomplished according to the ASTM E285‐08 . Experimental setup for ablation testing is displayed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Tate et al, Mirzapour et al, Srebrenkoska, and Srikanth et al prepared and evaluated the carbon‐phenolic composite, and Bahramian et al improvise it again with the addition of graphite and kaolinite. Pulci et al demonstrated the effective manufacturing of carbon‐phenolic composite for reentry space vehicles.…”
Section: Polymeric Materials As Ablatives In Thermal Protection: An Omentioning
confidence: 99%
“…Different types of polymeric ablatives can be summarized in of woven rayon and carbon black filler in phenolic matrix) developed by the Cytec Engineered Materials is the most famed material for the standardization of the National Aeronautics and Space Administration and other research federations. 37 Patton et al 38 Tate et al, 37 Mirzapour et al, 40 Srebrenkoska, 41 As a high-performance resin, epoxy has a popular trademark in the development of polymeric ablatives for insulator rocket motor casing.…”
Section: Polymeric Materials As Ablatives In Thermal Protection: Anmentioning
confidence: 99%
“…This is due to the complete elimination of the noncarbon species and char of coalesced carbon rings formation during pyrolysis. Evolution of gas during the pyrolysis mechanism is controlled by controlling the heating rate of the composite [72]. Clarity in the physiochemical reaction in pyrolysis mechanism leads to optimization of the factor of safety during the design of the composite heat shields.…”
Section: Pyrolysis Mechanism Of Carbon Based Polymer Matrixmentioning
confidence: 99%